2017
DOI: 10.13189/ujer.2017.050701
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Jigsaw Technique on the Students' Laboratory Material Recognition and Usage Skills in General Physics Laboratory-I Course

Abstract: This research aims to compare the effects ofJigsaw technique from the cooperative learning methods and traditional learning method on laboratory material recognition and usage skills of students in General Physics Lab-I Course. This study was conducted with 63 students who took general physics laboratory-I course in the department of science education at a state university in Turkey during 2012-2013 academic year. The randomly selected class 1-A consisting of 32 students was assigned as the experiment group (j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 14 publications
4
14
0
3
Order By: Relevance
“…Therefore, having acute interaction opportunities helped them learn mathematics skills effectively. These findings are also in line with the previous findings of the studies (Aydin, & Biyikli, 2017;Baroody, Clements & Sarama, 2019;Evcim & İpek, 2013).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, having acute interaction opportunities helped them learn mathematics skills effectively. These findings are also in line with the previous findings of the studies (Aydin, & Biyikli, 2017;Baroody, Clements & Sarama, 2019;Evcim & İpek, 2013).…”
Section: Resultssupporting
confidence: 93%
“…Through this strategy, students must feel themselves more comfortable with their roles. To evaluate the teams can develop the effectiveness of the jigsaw technique by working each learner have a sense of responsibility for their team's performances in the classroom (Aydin & Biyikli, 2017). In Jigsaw style, each learner prepares a part of the assignment outside the lesson.…”
Section: Literature Review Jigsaw Strategymentioning
confidence: 99%
“…Les apprentissages disciplinaires sont au coeur du processus. L'efficacité de cette méthode peut dépendre des types de contenus enseignés (Aydin & Biyikli, 2017;Er, 2017;Escalié et al, 2015;Karacop & Diken, 2017;Mengduo & Xiaoling, 2010…”
Section: Discussionunclassified
“…Aksoy & Doymuş (2011) found that that CL is more effective method than traditional teaching to learn the laboratory skills for 6 th graders. Jigsaw was also reported to significantly improve the laboratory skills of university students than traditional group method (Aydin & Biyikli, 2017) and significantly enhance the science process than confirmatory laboratory method (Karacop & Diken, 2017). Although the research on the effect of Jigsaw on science process skills is rare but the positive effect of different models of CL like learning together & group investigative models on science practical performance in laboratory has been proved by a number of studies (Díaz-Vazquez, et.…”
Section: Conclusion and Discussionmentioning
confidence: 99%